2015
DOI: 10.4166/kjg.2015.66.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Cervical Spine and Pelvic Bone Metastases Presenting as Unknown Primary Neoplasm

Abstract: The occurrence of hepatocellular carcinoma (HCC) is closely associated with viral hepatitis or alcoholic hepatitis. Although active surveillance is ongoing in Korea, advanced or metastatic HCC is found at initial presentation in many patients. Metastatic HCC presents with a hypervascular intrahepatic tumor and extrahepatic lesions such as lung or lymph node metastases. Cases of HCC presenting as carcinoma of unknown primary have been rarely reported. The authors experienced a case of metastatic HCC in a patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The most common presenting symptom was pain and neurological symptoms. Most of the reported cases in literature received surgical decompression while Sorafenib treatment was also discussed in literature [5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common presenting symptom was pain and neurological symptoms. Most of the reported cases in literature received surgical decompression while Sorafenib treatment was also discussed in literature [5]. …”
Section: Discussionmentioning
confidence: 99%
“…For most of the cases of cervical spinal cord involvement the underlying etiological hepatic risk factor appears to be hepatitis B infection. Most of the cases are reported from the east from areas of increased hepatitis B prevalence [35]. Nakamura et al [9] reported four cases of cervical cord compression due to HCC in whom he evaluated the response of metastasis to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Inaba et al 18 reported that gingival bleeding due to metastatic HCC in an 80-year-old man was controlled successfully after TACE until his death, which was due to respiratory failure. In our case, surgical resection, TACE or sorafenib could not be performed due to poor liver function and unstable coagulation state.…”
Section: Discussionmentioning
confidence: 99%
“…HCC and respiratory system cancers are the most common cause of cancer-related deaths in Taiwan [ 1 , 2 ]. HCC is the fourth highest cause of cancer-related death in Japan [ 3 ] and the fifth most common cancer diagnosed in Korea [ 4 ]. Due to better diagnosis, improvements in management, and prolonged survival of patients, an increasing number of patients are diagnosed after extrahepatic spread.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] 79 M n/a (paper from Greece) Hepatitis B (not on medications) Not mentioned Upper extremity muscle pain and paresthesia 31 2015 Hwang et al . [ 4 ] 61 M n/a (paper from South Korea) Hepatitis B AST 418 U/l ALT 594 U/l HBV DNA 1890769 copies/mL Upper extremity weakness and tingling 32 2016 Sangli et al . [ 14 ] 49 M Emigrant from Ghana Hepatitis B not on medications ALT and AST WNL Left lower extremity weakness and numbness 33 2017 Ayyadurai et al .…”
Section: Introductionmentioning
confidence: 99%